2020
DOI: 10.1016/j.celrep.2020.108144
|View full text |Cite
|
Sign up to set email alerts
|

LIM-Homeodomain Transcription Factor LHX4 Is Required for the Differentiation of Retinal Rod Bipolar Cells and OFF-Cone Bipolar Subtypes

Abstract: Retinal bipolar cells (BCs) connect with photoreceptors and relay visual information to retinal ganglion cells (RGCs). Retina-specific deletion of Lhx4 in mice results in a visual defect resembling human congenital stationary night blindness. This visual dysfunction results from the absence of rod bipolar cells (RBCs) and the loss of selective rod-connecting cone bipolar cell (CBC) subtypes and AII amacrine cells (ACs). Inactivation of Lhx4 causes the apoptosis of BCs and cell fate switch from some BCs to ACs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Based on previous reports, LHX4 is expressed in BCs and PRs of both mouse and chicken retinas. In mice, LHX4 is transiently expressed in the rod BCs and RPs of the developing retina and persistently expressed in the CPs, ON-cone BCs, and four subtypes of OFF-cone BCs (type 2, 3a, 3b, and 4) of the adult retina [34][35][36] . Buenaventura et al found that the conservation expression of LHX4 in early CPs of mouse and chicken retinas is a new marker of early CPs 37 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on previous reports, LHX4 is expressed in BCs and PRs of both mouse and chicken retinas. In mice, LHX4 is transiently expressed in the rod BCs and RPs of the developing retina and persistently expressed in the CPs, ON-cone BCs, and four subtypes of OFF-cone BCs (type 2, 3a, 3b, and 4) of the adult retina [34][35][36] . Buenaventura et al found that the conservation expression of LHX4 in early CPs of mouse and chicken retinas is a new marker of early CPs 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, no effect occurred on the differentiation of OFF-BCs (marked by vsx1), rod BCs (marked by PKCα and bhlhe23), and apoptosis (marked by activated-Caspase3) in the retina. In mice, Dong et al found that Lhx4 CKO (conditional knockout) results in the loss of rod BCs, rod-connecting BCs, and AII ACs, and a visual defect resembling the human CSNB (congenital stationary night blindness) 34 . Together, these findings demonstrate that Lhx4 plays an important role in vertebrate retinal development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations